(3GdefbP ef GdgdcI aj OaY eVGQ GdSehe GdegdcIs - (3GdMSf Hf CHj JZdH Hf GdeHGQc Hf CHj GdTQa, GdeJWHHs
(3ChdgG (B:s
(3HYO GdMeO ddg bGd GdMSjf Hf CHj JZdH Ef GdfYeI JRQY GdeMHI hcGf GdeTab dGjRGd ecdakG s
(3BNQgG (B:s
(3hjNdW eY eKdg eY eKdg YjT de jUjHg fGQ hjUeO ehVY GdYVg aEfg fGaY Ef TGA Gddg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B186 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1869s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs